Psychotherapists’ Challenges With Online Therapy During COVID-19: Concerns About Connectedness Predict Therapists’ Negative View of Online Therapy and Its Perceived Efficacy Over Time - Békés, Vera; Aafjes-van Doorn, Katie; Luo, Xiaochen; Prout, Tracy A.; Hoffman, Leon (Frontiers in Psychology, 2021)
Therapists’ forced transition to provide psychotherapy remotely during the COVID-19 pandemic offers a unique opportunity to examine therapists’ views and challenges with online therapy. This study aimed to investigate the main challenges experienced by therapists during the transition from in-person to online therapy at the beginning of the pandemic and three months later, and the association between these challenges and therapists’ perception of the quality of the relationship with their online patients, and therapists’ attitudes and views about online therapy and its efficacy at these two timepoints. As part of a large-scale international longitudinal survey, we collected data from 1,257 therapists at two timepoints: at the start of COVID-19, when many therapists switched from providing in-person therapy to online therapy, as well as three months later, when they had had the opportunity to adjust to the online therapy format. At both time points, therapists reported on perceived challenges, quality of working alliance and real relationship, attitudes towards online therapy, and their views on online therapy’s efficacy compared to in-person therapy. Factor analysis of individual survey items at both time points identified four different types of challenges among this therapist sample: Emotional connection (feeling connected with patients, reading emotions, express or feel empathy), Distraction during sessions (therapist or patient), Patients’ privacy (private space, confidentiality), and Therapists’ boundaries (professional space, boundary setting). Older and more experienced therapists perceived fewer challenges in their online sessions. At baseline, all four types of challenges were associated with lower perceived quality of the therapeutic relationship (working alliance and real relationship), and more negative attitudes towards online therapy and its efficacy. After three months, perceived challenges with three domains - Emotional connection, Patients’ privacy, and Therapists’ boundaries significantly decreased – whereas challenges in the fourth domain – Distraction – increased. In our study, therapists’ concerns about being able to connect with patients online appeared to be the most impactful, in that it predicted negative attitudes towards online therapy and its perceived efficacy three months later, above and beyond the effect of therapists’ age and clinical experience. Clinical and training implications are discussed.